Cryopreserved anti-CD22 and bispecific anti-CD19/22 CAR T cells are as effective as freshly infused cells - Alexandra Dreyzin; Sandhya R. Panch; Haneen Shalabi; Bonnie Yates; Steven L. Highfill; Ping Jin; David Stroncek; Nirali N. Shah (Molecular Therapy: Methods & Clinical Development, 2023)
Cryopreservation of chimeric antigen receptor (CAR) T cells facilitates shipment, timing of infusions, and storage of subsequent doses. However, reports on the impact of cryopreservation on CAR T cell efficacy have been mixed. We retrospectively compared clinical outcomes between patients who received cryopreserved versus fresh CAR T cells for treatment of B cell leukemia across two cohorts of pediatric and young adult patients: those who received anti-CD22 CAR T cells and those who received bispecific anti-CD19/22 CAR T cells. Manufacturing methods were consistent within each trial but differed between the two trials, allowing for exploration of cryopreservation within different manufacturing platforms. Among 40 patients who received anti-CD22 CAR T cells (21 cryopreserved cells and 19 fresh), there were no differences in in vivo expansion, persistence, incidence of toxicities, or disease response between groups with cryopreserved and fresh CAR T cells. Among 19 patients who received anti-CD19/22 CAR T cells (11 cryopreserved and 8 fresh), patients with cryopreserved cells had similar expansion, toxicity incidence, and disease response, with decreased CAR T cell persistence. Overall, our data demonstrate efficacy of cryopreserved CAR T cells as comparable to fresh infusions, supporting cryopreservation, which will be crucial for advancing the field of cell therapy.